The Mediating Effect of Technical Efficiency on the Relationship between Revenue Diversification and Financial Performance of Commercial Banks in Kenya - Teimet, Paul; Josephat, Lishenga; Mwangi, Iraya; Duncan, Elly (European Scientific Journal, ESJ, 2020)
Banks generate revenue through the intermediation process and perceive revenue diversification as a possible solution to financial performance challenges. The banks’ income statements attest to this argument with banking activities moving gradually from interest-bearing activities to non-interest-bearing activities. The objectives of this paper were to assess the relationship between revenue diversification and return on assets and establish the mediation effect of technical efficiency on the relationship between revenue diversification and return on assets. The research used unbalanced panel data sourced from forty-two commercial banks spanning 2009 to 2018. The study measured revenue diversification using the Hirschman-Herfindahl index while technical efficiency level was measured using data envelopment analysis. The performance attribute, return on assets was measured as a ratio of earnings before interest and tax over the total assets. The paper assessed the relationships using the panel least square regression guided by the mediation assessment process proposed by Baron and Kenny. The cross-section randomeffects model results revealed a significant positive relationship between revenue diversification and return on assets. Further, results indicated the absence of technical efficiency mediation effect on the relationship between revenue diversification and return on assets. The study recommends policy and regulatory programs that allows banks to diversify in revenue-generating activities as well as initiatives that synchronize technical efficiency in the intermediation process to improve financial performance of commercial banks, especially in emerging economies.